2001
DOI: 10.1046/j.1365-2958.2001.02616.x
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of luxS affects growth and virulence factor expression in Streptococcus pyogenes

Abstract: Adaptive responses of bacteria that involve sensing the presence of other bacteria are often critical for proliferation and the expression of virulence characteristics. The autoinducer II (AI‐2) pathway has recently been shown to be a mechanism for sensing other bacteria that is highly conserved among diverse bacterial species, including Gram‐positive pathogens. However, a role for this pathway in the regulation of virulence factors in Gram‐positive pathogens has yet to be established. In this study, we have i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
91
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(99 citation statements)
references
References 63 publications
2
91
0
1
Order By: Relevance
“…[30][31][32][33][34][35][36]55 Furanone-1 [(5Z)-4-bromo-5-(bromomethylene)-3-butyl-2(5H)-furanone] has been shown to inhibit >70% of the AI-2 regulated genes in E. coli, has been observed in Streptococcus pyogenes. 50 In total, these data demonstrate that the altered phenotypes in the ∆luxS strain are due to luxS disruption and not to other undefined coincident mutations.…”
Section: Discussionmentioning
confidence: 63%
“…[30][31][32][33][34][35][36]55 Furanone-1 [(5Z)-4-bromo-5-(bromomethylene)-3-butyl-2(5H)-furanone] has been shown to inhibit >70% of the AI-2 regulated genes in E. coli, has been observed in Streptococcus pyogenes. 50 In total, these data demonstrate that the altered phenotypes in the ∆luxS strain are due to luxS disruption and not to other undefined coincident mutations.…”
Section: Discussionmentioning
confidence: 63%
“…Consequently, in our study we examined for the suitability of such heterologous complementation in a Gram-positive bacterium. This could be of broad interest because in several single and multispecies studies, especially on human pathogenic streptococci, a multitude of effects was observed, investigating luxS deletion mutants; in the exclusively human pathogen Streptococcus pyogenes, LuxS mutation had a pronounced effect on many virulence traits, including hemolytic and proteolytic activity as well as acid tolerance (17)(18)(19). Similar pleiotropic effects were observed in another important human pathogen, Streptococcus pneumoniae.…”
mentioning
confidence: 86%
“…Clostridium are noted to contain either single or multiple QSS, such as: (1) LuxS, (2) Agr, (3) Agr2 that are regulated by peptide signals e.g., AIP ( Table 1) [24][25][26][27][28][29]. Table 1) [30][31][32][33][34].…”
Section: Clostridiummentioning
confidence: 99%